Architectural adaptations of muscle to training and injury: a narrative review outlining the contributions by fascicle length, pennation angle and muscle thickness. Issue 23 (27th January 2016) - Timmins, Ryan G; Shield, Anthony J; Williams, Morgan D; Lorenzen, Christian; Opar, David A
Abstract : Background: The architectural characteristics of muscle (fascicle length, pennation angle muscle thickness) respond to varying forms of stimuli (eg, training, immobilisation and injury). Architectural changes following injury are thought to occur in response to the restricted range of motion experienced during rehabilitation and the associated neuromuscular inhibition. However, it is unknown if these differences exist prior to injury, and had a role in injury occuring (prospectively), or if they occur in response to the incident itself (retrospectively). Considering that the structure of a muscle will influence how it functions, it is of interest to understand how these architectural variations may alter how a muscle acts with reference to the force-length and force-velocity relationships. Objectives: Our narrative review provides an overview of muscle architectural adaptations to training and injury. Specifically, we (1) describe the methods used to measure muscle architecture; (2) detail the impact that architectural alterations following training interventions, immobilisation and injury have on force production and (3) present a hypothesis on how neuromuscular inhibition could cause maladaptations to muscle architecture following injury.